Dielectric and piezoelectric properties of 1-3 non-lead barium zirconate titanate-Portland cement composites - Potong R. (2014)
Non-lead barium zirconate titanate (BZT)-Portland cement (PC) composites have been seen as promising new non-lead composites. This paper reports research work on the dielectric and piezoelectric properties of 1-3 non-lead barium zirconate titanate (BZT)-Portland cement (PC) composites. The 1-3 non-lead composites with different BZT contents at 40-70% by volume were fabricated by the dice-and-fill method. The results show that the dielectric loss of the 1-3 non-lead composite was lowest at 0.08 at 70% BZT composites. The models are applied for the calculation with the dielectric constant, piezoelectric coefficient and piezoelectric voltage constant and the results were found to fit closest to that of the parallel model. At 70% BZT content or higher, piezoelectric coefficient was found to have values higher than 130 pC/N. In addition, the new 1-3 non-lead composites can be tuned to an ideal compatible value that match the requirement of concrete structure. © 2012 Elsevier Ltd and Techna Group S.r.l.